76‐1: Invited Paper: Optimization of Applied Materials PiVotTM Array Coater for Metal Oxide Semiconductor Layers. Issue 1 (May 2017) - Park, Hyun Chan; Kloeppel, Andreas; Bhoolokam, Ajay Sampath; Hanika, Markus; Bender, Marcus; Busch, John D; Hsu, Hao-Chien; Yim, Dong Kil
Abstract : Applied Materials' static PVD array coater using rotary targets has been developed to provide less in‐film particle, high target utilization performance by novel rotary target technology and uniform layer deposition by unique magnet motion in display industry. It has been optimized to provide highly stable and uniform thin metal oxide layer to reach uniform TFT performance for large area substrate (2500x2200mm glass size).